Electronic Structure of Graphene Grown on a Hydrogen-terminated Ge (110) Wafer - Ahn, Sung Joon; Kim, Hyun Woo; Khadka, Ishwor Bahadur; Rai, Krishna Bahadur; Ahn, Joung Real; Lee, Jae Hyun; Kang, Seog Gyun; Whang, Dongmok (Journal of the Korean Physical Society, 2018)
Using angle-resolved photoemission spectroscopy, we studied the electronic structure of graphene grown on a Ge (110) wafer, where a single-crystal single-layer graphene was recently grown using chemical vapor deposition. The growth mechanism of the single-layer single-crystal graphene was related to the hydrogen termination of the Ge (110) surface. To further understand the growth mechanism, we measured the electronic structure of the graphene-covered Ge (110) wafer in a vacuum as a function of the increasing temperature, which led to a deintercalation of the hydrogen atoms. Furthermore, we measured the electronic structure after the reintercalation of the hydrogen atoms between the Ge substrate and graphene. These findings show that hydrogen is intercalated between the Ge substrate and graphene after the growth of graphene using chemical vapor deposition.
Keywords: Angle-resolved photoemission spectroscopy; Chemical vapor deposition; Graphene